Formation of Lexical and Sociocultural Competence of Future Translators Based on the Terminology of Historical Costumes from the Chernihiv Region - Pikun, Lesia (Educological discourse, 2026)
The article examines student educational translation practice as an essential stage of future professional training, facilitating the practical reinforcement of knowledge gained through the English Language Practice course. The research objective is to substantiate the appropriateness of implementing research-based student projects and developing methodological approaches for shaping the lexical and sociocultural competence of future translators based on the historical and cultural material of the Chernihiv region. The author of the article proposes a series of research projects on the topic ‘Clothing of different eras in the Chernihiv region,’ which combines linguistic, cultural, historical, and translation aspects. The study validates the effectiveness of using local cultural heritage as a source of vocabulary and a tool for developing sociocultural competence. The article outlines a step-by-step model for organising educational translation practice, including preparatory, main and final stages with relevant activities: compiling a thematic glossary, searching for English equivalents of Ukrainian costume terms, describing museum artefacts, and creating Multimedia presentations. Special attention is given to the collections of the Chernihiv Regional Historical and Art Museums as sources of material for working with specialised vocabulary. The project experience enables students not only to consolidate their language knowledge but also to develop academic research skills, information analysis and synthesis, visual description, and translation of culturally marked concepts. The article also highlights future research perspectives in the area of interdisciplinary integration within philological internship programmes, particularly by expanding the range of research topics.